Judge Frank Creede, Jr. Swears In Superior Court Judge Mario Olmos - Watkins, Howard::::::::: (1983)
Judge Frank Creede, Jr., Mario Olmos, Mary Louise Frampton holding Margaret Olmos, Daniel Olmos, Mario's mother Delores Olmos and father Fidel Olmos Law Offices of Olmos and Frampton at 925 N St. #150, Fresno